Social Participation and Quality of life of Rural Elderly Living in Community Dwelling in Nepal - Joshi, Mahendra Raj (NUTA Journal, 2020)
The concept of social participation integrates with the policy of active ageing along with health and security. It encourages and advocates the productive engagement of elderly and acknowledges their potential contribution in the society. The main objective of this paper is to explore the status of social participation and its influence on their quality of life of older people living in community dwelling in Nepal. A cross-sectional community-based survey was carried out (November-December 2017) among 547 randomly selected 60 years and older people living in community dwelling. Quality of life (QOL) was measured by using the World Health Organization Quality of Life-abbreviated scale and social participation was measured by asking direct questions related to their participation in publing meeting, and perception about social relations in last one year.  Descriptive technique was used to analyze the data. One way ANOVA was performed to explain the significance of differentials in quality of life and its dimension among older people.vThe findings shows majority (52.9%) of males and  less than half of  females  (37.9%%)  who have attended any types of publing in last one year. This study found QOL score of Nepalese elderly was 12.92. It shows quality of life of Nepalese elderly was moderate level (with in the range of 4-20 scales). The mean scores of overall QOL index of elderly people who have attended public meeting was observed significantly higher (M=13.72) compared to those who did not attend of any public meeting (M= 12.29). Elderly social participation have significantly better quality of life in Nepal. This suggests the need to improve the frequency of participation of elderly people to their community which provides them opportunities to interact more with their physical as well as social environment that consequently improved their overall QOL.